Woven EndoBridge Intrasaccular Flow Disrupter for the Treatment of Ruptured and Unruptured Wide-Neck Cerebral Aneurysms: Report of 55 Cases - Behme, D.; Berlis, A.; Weber, W. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The safety and efficacy of the Woven EndoBridge (WEB) device for the treatment of cerebral aneurysms have been investigated in several studies. Most of these studies focused on specific aneurysms or a certain WEB device. Our objective was to report the experience of 2 German centers with the WEB device, including technical feasibility, safety, and short-term angiographic outcome.MATERIALS AND METHODS: We performed a retrospective study of all ruptured and unruptured aneurysms that were treated with a WEB device (WEB Double-Layer, Single-Layer, and Single-Layer Sphere) between April 2012 and August 2014. Primary outcome measures included the feasibility of the implantation and the angiographic outcome at 3-month follow-up. Secondary outcome measures included the clinical outcome at discharge and procedural complications.RESULTS: Fifty-five aneurysms in 52 patients, including 14 ruptured aneurysms, underwent treatment with the WEB device. The median age of patients was 55 years (range, 30–75 years); 19/55 (37%) were men. The device could be deployed in all patients and was implanted in 51/55 (93%) cases. Procedural complications occurred in 6/51 (12%), comprising 2 thromboembolic events, 2 thrombus formations, 1 high-grade posterior cerebral artery stenosis, and 1 aneurysm rupture. None of these had clinical sequelae. Angiographic follow-up at 3 months was available for 44/51 (86%) aneurysms. A favorable angiographic result at 3 months was achieved in 29/44 (66%) cases, whereas the percentage of good anatomic results increased from 40% in 2012 to 75% in 2014.CONCLUSIONS: The WEB device proved to be safe. Acceptable occlusion rates can be achieved but seem to require wide experience with the device.ASAacetylsalicylic acidDLDouble-LayerSLSingle-LayerSLSSingle-Layer SphereWEBWoven EndoBridge